Mrs Malaprop Goes to Hastings: History, Parody, and Language in 1066 and All That (1930) (Altre Modernità, 2017)
This essay discusses the manifold ways in which malapropisms, among other strategies, contribute to the comic effects achieved in 1066 and All That, a book meant to satirize early twentieth-century history manuals. After an overview of the book’s structure and contents, I will highlight examples in which linguistic choices cause semantic shifts resulting in humorous remarks. These typically sound like misremembered facts or mispronounced names, in a flurry of statements evoking the idiosyncratic usage of Mrs Malaprop, Richard Sheridan’s famous character. Throughout the text it is however difficult to draw a line between mere spoof and thinly-veiled ideological criticism: in carnivalesque uses, the maxims that underpin the Cooperative Principle can hardly apply, and reading between the lines, or indeed among semantic clusters, is indispensable.